GENERALIZED ERUPTIVE SYRINGOMAS - Jamalipour, Mahnaz (Medknow Publications, 2009)
Generalized eruptive syringoma is a rare clinical presentation of a benign adnexal tumor that derives from the intraepidermal portion of the eccrine sweat ducts. It presents as successive crops of small flesh-colored papules on the anterior body surfaces. It generally occurs in the peripubertal period. Treatment of this benign condition is cosmetic only. A case of a 28-year-old female with an eight-year history of eruptive syringoma is presented.